Knee and hip muscle strength of male soccer players from different competitive levels - França, C.; Martins, F.; Przednowek, K.; Marques, A.; Ihle, A.; Sarmento, H.; Gouveia, É.R. (Journal of Human Kinetics, 2024)
In soccer, knee and hip muscle strength assessments have been recommended for injury prevention. The aims of this study were threefold: (1) to compare knee and hip muscle strength between professional players competing at different levels; (2) to compare strength performance according to the preferred leg (PL) and the non-preferred leg (NPL); and (3) to compare knee and hip muscle strength performance at two moments of the season. This study included 33 professional soccer players: 13 were in the elite group (EG), and 20 were in the sub-elite group (SEG). Body composition, isokinetic knee strength at 60º/s, and hip adduction strength were assessed at two different moments (M1 and M2). Values of peak torque (PT), peak torque/bodyweight (PT/BW), and the hamstring-to-quadriceps strength ratio (H:Q) for knee extensors (KEs) and knee flexors (KFs) for both legs were used for analysis. The statistical analysis included the Mann-Whitney U and the Wilcoxon Signed Rank tests. At M1, the EG presented a significantly better performance in KF PT/BW and in the squeeze strength test for the PL and the NPL (p 0.01). At M2, the EG performed substantially better in KE PT/BW and KF PT/BW (p 0.01). No substantial strength differences were observed in knee and hip muscle performance between the PL and the NPL. From M1 to M2, significant increases were found in knee strength in both groups (p 0.01). Overall, the EG players outperformed significantly their lower-division peers in strength assessments. The results indicate significant knee and hip muscle strength increases during the season, probably as a response to the exposure to training and competition.